2022
DOI: 10.1101/2022.07.25.501382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient generation of marmoset primordial germ cell-like cells using induced pluripotent stem cells

Abstract: Reconstitution of germ cell fate from pluripotent stem cells provides an opportunity to understand the molecular underpinnings of germ cell development. Here, we established robust methods for pluripotent stem cells (iPSCs) culture in the common marmoset (Callithrix jacchus, cj), which stably propagate in an undifferentiated state. Notably, iPSCs cultured on a feeder layer in the presence of a WNT signaling inhibitor upregulated genes related to ubiquitin-dependent protein catabolic processes and enter a permi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although rare hPGC-LC surface markers were identified such as CD38 [ 14 ], difficulties to sort germ cells are still encountered and alternative surface markers are lacking. It was previously reported that PDPN distinguishes early PGC from gonadal somatic cells in humans and marmosets [ 26 , 27 , 28 ]. ScRNA-seq indicates that PDPN was strongly expressed and CD38 was very weakly detected in PGC-LC ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 99%
“…Although rare hPGC-LC surface markers were identified such as CD38 [ 14 ], difficulties to sort germ cells are still encountered and alternative surface markers are lacking. It was previously reported that PDPN distinguishes early PGC from gonadal somatic cells in humans and marmosets [ 26 , 27 , 28 ]. ScRNA-seq indicates that PDPN was strongly expressed and CD38 was very weakly detected in PGC-LC ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the concentration of BMP4 should be refined for individual ES cell clones, at least in cattle and rhinoceroses. bPGCLCs expressed transcription factors important for PGC specification, such as BLIMP1, TFAP2C, SOX17, and NANOS3 [2,[4][5][6][7]10]. In contrast, SOX2 was not expressed in the bPGCLCs (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Recent reports have demonstrated that primordial germ cells (PGCs), the precursor cell population of gametes, are induced from ES/iPS cells in mammalian species including humans, monkeys, rabbits, rats, and rhinoceroses [2][3][4][5][6][7][8][9][10]. However, in vitro gametogenesis remains underdeveloped for use in livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Species difference or different methods used likely account for the discrepancy of the effect of BLIMP1 . Recently, another group reported marmoset PGCLC induction from PSCs (Seita et al, 2022). Their induction efficiency was 40% at the highest using a similar method reported in Cynomolgus monkeys and rabbits (Kobayashi et al, 2021; Sakai et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%